Pola Rekrutmen Pemilihan Calon Anggota Legislatif oleh Partai Demokrasi Indonesia Perjuangan (Pdi Perjuangan) Menjelang Pemilu 2014 di Kota Semarang - Ariwibowo, Hendri; Setyono, Budi; Martini, Rina (Journal of Politic and Government Studies, 2013)
Indonesian political parties are institutions that considered an institution withmodern democratic system. Therefore, political parties are obliged to conductrecruitment for Legislative Candidates, mostly party cadres that would be placed inParliament. Partai Demokrasi Indonesia Perjuangan (PDI Perjuangan) prior to theelection of 2014 has a policy of recruiting Candidate Legislatif through a mechanismeand more rigorous process according to Letter of Decree No.: 061 / TAP / DPP / III /2013. Thus, it can be expected to form best representatives in 2014 election, at anylevel of national Parliament, Provincial and City / District.This study aims to determine the pattern of recruitment conducted by PDIPerjuangan in Semarang. The method used in this study is qualitative method. Thedata is collected by in-depth interview to several representative in formants anddocumentation. Analyzes of the data based on the interview.The result showsd that the recruitment pattern of legislative candidate for2014 election conducted by the DPC PDI Perjuangan Semarang was bya on ordersDPP. Based on party rules that have been listed in the Letter of Decree No: 061 / TAP/ DPP / III / 2013. The regulation stated that the recruitment pattern of legislativecandidates must go through the process of registration, networking, administrationtest (psychological, and understanding of party ideology), screening as well asassignments.It can be concluded, that the members of legislative candidates must followthe rules of the party in the recruitment process. Start of the registration process,networking and filtering. While the constraints experienced by DPC PDI Perjuanganin recruiting members of the legislature are in the process of screening for adiscussion of this process is difficult for the parties to determine the names of thecandidates according to the criteria of the party.Keywords: Party Regulation, Registration, Networking, Filtering, Determination